Pseudomonas associated with Bursaphelenchus xylophilus, its insect vector and the host tree: A role in pine wilt disease? - Alves, Marta (2020)
In this study, we characterized the diversity of Pseudomonas associated with Bursaphelenchus xylophilus, its insect vector (Monochamus galloprovincialis) and its host (Pinus pinaster), by a culture‐independent approach using rpoD clone libraries. Clone libraries of Pseudomonas rpoD were obtained from B. xylophilus, M. galloprovincialis and infected P. pinaster. Most M. galloprovincialis and B. xylophilus sequences grouped together in the P. fluorescens group. Genes related to xenobiotics degradation and phenylacetate synthesis were present in the genomes of the type strains closely related to sequences retrieved from the nematode libraries. Results demonstrated that the nematode, during its life stages inside the tree, maintains a diverse Pseudomonas community that is closely related to the one associated with the insect vector. These bacteria might contribute to degradation of xenobiotics and tree weakening during the nematode tree infection.